2015
DOI: 10.1007/s13312-015-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing verbal intelligence and spoken language in children with phenylketonuria

Abstract: The study confirmed that diagnosis of newborns and control of blood phenylalanine concentration improves verbal intelligence and spoken language scores in phenylketonuria subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Although children with phenylketonuria who are treated early have average intelligence, they differ in cognitive performance when compared with their peers without phenylketonuria. Academic and cognitive functions of children with phenylketonuria are significantly lower than peers in the control group (2). It has also been reported that children with phenylketonuria may have low self-esteem, less motivation, loss of independence and reduced social confidence.…”
Section: Introductionmentioning
confidence: 95%
“…Although children with phenylketonuria who are treated early have average intelligence, they differ in cognitive performance when compared with their peers without phenylketonuria. Academic and cognitive functions of children with phenylketonuria are significantly lower than peers in the control group (2). It has also been reported that children with phenylketonuria may have low self-esteem, less motivation, loss of independence and reduced social confidence.…”
Section: Introductionmentioning
confidence: 95%
“…Phenylketonuria (PKU) is the most common hereditary metabolic disorder in the world (1). Patients with PKU show high levels of phenylalanine in the blood serum, and thus develop neurological disorders such as mental retardation, seizures, behavioral problems, and developmental delays (2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PKU is high in Iran (2); thus, the incidence of the disease was 1 in 10,000 in the Karamifar et al study (7) and 1.6 in 10,000 in the Habib et al study (8). The PKU screening program began in Iran in 2006 and blood samples of newborns are taken on the third to fifth days of birth for screening, and newborns with a phenylalanine level of 4 mg/dL or higher are referred for HPLC test for diagnosis confirmation.…”
Section: Introductionmentioning
confidence: 94%
“…Accumulation of phenylalanine and its metabolites without appropriate intervention during infancy leads to the occurrence of progressive cognitive-neurological damages in newborns (1). High levels of phenylalanine in the plasma typically cause mental disability, seizure, behavioral problems, and delay in motion and language evolution (2). The incidence of PKU may vary in different ethnic communities.…”
Section: Introductionmentioning
confidence: 99%